The Proportions of Truth - Hoare, Edward, 1812-1894 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Proportions of Truth" by Edward Hoare is a theological treatise written in the late 19th century. This work examines the essential harmony and balance within religious truths, arguing that exaggeration or distortion can lead to heresy, emphasizing the need for proportionate understanding of scriptural principles. The author draws on various disciplines such as art, nature, and music to illustrate how proportions are fundamental not only in faith but in all forms of existence. In "The Proportions of Truth," Hoare articulates a vision of Christian faith whereby the truths presented in scripture must be understood in relation to one another to achieve a faithful representation of God's revelation. He explores themes such as the importance of balancing different attributes of God, the roles of ritual versus reality in worship, and the significance of the sacraments. Throughout the book, he emphasizes that a partial view of truth, whether through selective teachings or previously held traditions, diminishes the complete message of the Gospel. He argues for a holistic approach that integrates the varied aspects of Christian doctrine to foster a deeper, more harmonious faith among believers. (This is an automatically generated summary.)
Release date is 2016-08-08
Transcribed from the 1872 William Hunt and Company edition by David Price
Keywords: Church of England -- Customs and practices; Ritualism; Church of England -- Doctrines